Os aplicativos educacionais à luz da pedagogia histórico-crítica no ensino e na aprendizagem de matemática - Duarte, Paulo César Vieira (2024)
The present research is a Stricto Sensu Professional Master's dissertation, linked to the research line Methodological theoretical conceptions and teaching practices, of the Postgraduate Program in Teaching in Basic Education (PPGEEB) of the Center for Teaching and Research Applied to Education (Cepae) from the Federal University of Goiás (UFG). This study investigated the use of educational applications for teaching work, in the light of Historical Critical Pedagogy (PHC), in Mathematics classes in the final years of Elementary School (EF). The research was conducted using a qualitative approach, carried out in the field, with one teacher and 27 students from a ninth-grade PE class at Escola Maria de Lourdes Estivalet Teixeira, located in the municipality of Goiatuba, Goiás. The problem question that guided this research was the following: What are the didactic contributions of educational applications, in light of PHC, for teaching work in the teaching and learning process of Mathematics in the final years of EF? The general objective was to analyze the pedagogical possibilities of educational applications as teaching resources, in the light of PHC, in Mathematics classes in the final years of EF. To this end, the methodological proposal began the construction of the theoretical framework, which included several authors, such as: Araújo (2020), Conceição (2018), Cysneiros (1999), Deslandes, Gomes and Minayo (2009), Gasparin (2012), Giardinetto (2021), Gil (2008), Lakatos and Marconi (2003), Marsiglia (2011), Marx (1987; 2014), Moraes (2014; 2016, Moraes and Peixoto (2017), Moraes, Bueno and Do Nascimento (2017), Nascimento (2016), Peixoto and Moraes (2017), Peixoto (2012; 2016; 2022), Petenucci (2008), Saviani and Duarte (2021), Saviani (2021a; 2021b), Toschi (2005; 2019), Toschi et al. (2010), among others. For data collection, five types of instruments were used: semi-structured interviews, questionnaires, participant observation, field diary and assessments. Training was carried out with the teacher participating in the research on PHC teaching. After curating applications for cell phones, GeoGebra was chosen to implement a teaching project, and the content worked on in the classroom was 1st grade Systems of Equations. From the process of pedagogical discussion throughout the research, the development of the educational product “An approach to Historical-Critical Pedagogy in Teaching Practice” emerged, resulting in a didactic pedagogical material (e-book). It is presented as a pedagogical support material for Mathematics teachers in the integration of educational applications in the light of PHC in the teaching and learning of Mathematics. Therefore, it appears that there were didactic contributions by offering visual and interactive resources that helped students understand mathematical content in a more dynamic and interactive way. They also enabled the personalization of teaching, immediate result to students, in addition to encouraging student participation, making Mathematics classes more interesting and motivating, increasing interest and enthusiasm for the subject. The results of this study can contribute to pedagogical practices, but future research can deepen the investigation and even consider the long-term impact. Collaboration between schools, teachers, researchers and developers is a possibility to be considered.